The Role of Islam Religious Scholars in Politics - Syeda Dur e Nayab haider (Universitas Islam Internasional Indonesia (UIII), 2025)
Usaama al-Azami’s Islam and the Arab Revolutions: The Ulama Between Democracy and Autocracy represents a significant contribution to the growing body of literature examining the political role of religious scholars in the modern Muslim world, particularly in the context of the Arab Spring. Published in 2022 by Oxford University Press, the book seeks to disturb centuries-old presumptions over the